1355. Cluster of Multi-drug Resistance Neisseria gonorrhoeae Isolates with Reduce Ceftriaxone Susceptibility, First Report in Thailand. (4th December 2021) - Wannigama, Dhammika Leshan; Kueakulpattana, Naris; Luk-In, Sirirat; Hongsing, Parichart; Hurst, Cameron; Badavath, Vishnu Nayak; Jenjaroenpun, Piroon; Wongsurawat, Thidathip; Teeratakulpisan, Nipat; Kerr, Stephen J; Abe, Shuichi; Pearson, Lachlan; et al.
Abstract: Background: Rapid emergence of global azithromycin resistance, with ceftriaxone reduce susceptibility/resistant strains, threatens the current recommends dual therapy with ceftriaxone and azithromycin for gonorrhea to ensure effective treatment. Thailand is a major risk area for gonorrhea because it as a key destination for sex tourism industry, where antibiotic resistance gonorrhea can spread easily and quickly across the region. Here, we identified a first cluster of Neisseria gonorrhoeae isolates with decreased ceftriaxone susceptibility in Thailand. Methods: A 134 N. gonorrhoeae isolates collected from Thai Red Cross Anonymous Clinic, Bangkok, during 2016–2018 were studied. Broth micro-dilution and plate dilution methods to define resistance or decreased susceptibilityaccording to CLSI guidelines. Select isolates were subjected to whole genome sequencing with an Illumina MiSeq V2 instrument and analysis using CLCBio Genomics Workbench v6.5. Molecular docking studies were carried out to understand binding mode analysis and orientation of ceftriaxone in the active site of PBP2. Biofilm formation measured by confocal laser scanning microscopy. Results: Among the N. gonorrhoeae clinical isolates, two isolates had significant reduced susceptibility to ceftriaxone (MICs of 0.125 mg/L), which were isolated from urethral swab in male heterosexual patients. Both were multidrug resistance and strong biofilm producers with ceftriaxone tolerance (MBEC > 128 mg/L). One isolate was resistant to azithromycin (MIC of 1 mg/L), and other one remained susceptible (MIC of 0.5 mg/L). Reduced susceptibility to ceftriaxone associated with alterations in PBP2, PBP1, PorB, MtrR, and mtrR promoter region with one belonged to ST7235 and second one had new allele number of tbpB with new sequence type (ST). Ceftriaxone weakly occupy the active site of mosaic XXXIV penicillin-binding protein 2 (PBP2) variant in both. Molecular epidemiology results reviled that both isolates display similarities with isolates from UK, USA, and Netherlands. Conclusion: This first cluster of genetically related gonococcal isolates with decreased ceftriaxone susceptibility may bring threat of treatment failure in Thailand. Also highlighted the importance of maintaining surveillance for antimicrobial resistance. Disclosures: All Authors : No reported disclosures